2007
DOI: 10.1152/ajplung.00281.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acid aspiration-induced lung inflammation and injury are exacerbated in NADPH oxidase-deficient mice

Abstract: SM, Knight PR 3rd. Acid aspiration-induced lung inflammation and injury are exacerbated in NADPH oxidase-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
3
43
0
Order By: Relevance
“…Some studies have implicated ROS as a key element in the pathogenesis of ALI/ARDS following gastric content aspiration in mouse models [100], but to date, only one has demonstrated the role of NOX enzyme in this context. Indeed, exposure of p47 phox -deficient mice to HCl leads to increased pulmonary neutrophilic infiltration, alveolarcapillary barrier leakage, and enhanced level of proinflammatory cytokine compared to WT mice [101], suggesting a protective role of NOX2 in HCl-induced lung injury by modulating the inflammatory response.…”
Section: Epithelium and Endothelium Targetsmentioning
confidence: 99%
“…Some studies have implicated ROS as a key element in the pathogenesis of ALI/ARDS following gastric content aspiration in mouse models [100], but to date, only one has demonstrated the role of NOX enzyme in this context. Indeed, exposure of p47 phox -deficient mice to HCl leads to increased pulmonary neutrophilic infiltration, alveolarcapillary barrier leakage, and enhanced level of proinflammatory cytokine compared to WT mice [101], suggesting a protective role of NOX2 in HCl-induced lung injury by modulating the inflammatory response.…”
Section: Epithelium and Endothelium Targetsmentioning
confidence: 99%
“…Genetic mutations in NOX2 (gp91phox), p47phox, p67phox and p22phox are known to be responsible for development of CGD, but minimal evidence exists for associations of these polymorphisms with other diseases, and a recent analysis failed to show an association of polymorphisms within gp91phox, p47phox, p67phox or p22phox with infectious or non-infectious lung diseases, such as tuberculosis or sarcoidosis (199). Attempts to implicate NOX2 or p47phox in models of lung inflammation and injury, using gp91phox−/− or p47phox−/− mice, demonstrated that genetic NADPH oxidase deficiency was in many cases associated with enhanced inflammation and injury (200)(201)(202)(203), implicating that NOX2 also has beneficial functions in regulating inflammatoryimmune responses. For example, infection of gp91phox−/− mice with the yeast C. neoformans or with influenza virus was in either case found to result in increased Th1-skewed inflammation and granuloma formation, compared to their wild-type counterparts, which led to increased influenza clearance and protection against C. neoformans infection (204,205).…”
Section: Nox2mentioning
confidence: 99%
“…Deficiency of NOX2 in humans results in chronic granulomatous disease characterized by multiple abscess formation due to the inability of bacterial pathogens to be removed. However, in animal studies of chronic injury, NOX deficiency was associated with enhanced inflammation and subsequent tissue damage [9][10][11][12][13], implying that NOX2 also has beneficial functions in immune responses and cell signaling. Several studies have demonstrated that the superoxide generated by NOX2 is a key step in the development of endothelial cell dysfunction and functions by altering vascular tone and modulating cell signaling pathways [14][15][16][17].…”
Section: Superoxidementioning
confidence: 99%